Metabolic characterization of human IDH mutant and wild type gliomas using simultaneous pH- and oxygen-sensitive molecular MRI. Issue 9 (4th May 2019) - Yao, Jingwen; Chakhoyan, Ararat; Nathanson, David A; Yong, William H; Salamon, Noriko; Raymond, Catalina; Mareninov, Sergey; Lai, Albert; Nghiemphu, Phioanh L; Prins, Robert M; Pope, Whitney B; Everson, Richard G; et al.
Abstract: Background: Isocitrate dehydrogenase 1 (IDH1) mutant gliomas are thought to have distinct metabolic characteristics, including a blunted response to hypoxia and lower glycolytic flux. We hypothesized that non-invasive quantification of abnormal metabolic behavior in human IDH1 mutant gliomas could be performed using a new pH- and oxygen-sensitive molecular MRI technique. Methods: Simultaneous pH- and oxygen-sensitive MRI was obtained at 3T using amine CEST-SAGE-EPI. The pH-dependent measure of the magnetization transfer ratio asymmetry (MTRasym ) at 3 ppm and oxygen-sensitive measure of R2 ' were quantified in 90 patients with gliomas. Additionally, stereotactic, image-guided biopsies were performed in 20 patients for a total of 52 samples. The association between imaging measurements and hypoxia-inducible factor 1 alpha (HIF1α) expression was identified using Pearson correlation analysis. Results: IDH1 mutant gliomas exhibited significantly lower MTRasym at 3 ppm, R2 ', and MTRasym xR2 ' ( P = 0.007, P = 0.003, and P = 0.001, respectively). MTRasym xR2 ' could identify IDH1 mutant gliomas with a high sensitivity (81.0%) and specificity (81.3%). HIF1α was positively correlated with MTRasym at 3 ppm, R2 ' and MTRasym xR2 ' in IDH1 wild type ( r = 0.610, P = 0.003; r = 0.667, P = 0.008; r = 0.635, P = 0.006), but only MTRasym xR2 ' in IDH1 mutant gliomas ( r = 0.727, P = 0.039). Conclusions: IDH1 mutant gliomas have distinct metabolic and microenvironment characteristics compared with wild type gliomas. An imaging biomarker combining tumor acidity and hypoxia (MTRasym xR2 ') can differentiate IDH1 mutation status and is correlated with tumor acidity and hypoxia.